Depression risk in female patients with osteoporosis in primary care practices in Germany. Issue 9 (September 2016) - Drosselmeyer, J.; Rapp, M.; Hadji, P.; Kostev, K.
Abstract Summary Thirty-five thousand four hundred eighty-three female osteoporosis patients were compared with 35, 483 patients without osteoporosis regarding the incidence of depression. The risk of depression is significantly increased for patients with osteoporosis compared with patients without osteoporosis in primary care practices within Germany. Introduction The objectives of the present study were to analyze the incidence of depression in German female patients with osteoporosis and to evaluate the risk factors for depression diagnosis within this patient population. Methods This study was a retrospective database analysis conducted in Germany utilizing the Disease Analyzer® Database (IMS Health, Germany). The study population included 70, 966 patients between 40 and 80 years of age from 1072 primary care practices. The observation period was between 2004 and 2013. Follow-up duration was 5 years and was completed in April 2015. A total of 35, 483 osteoporosis patients were selected after applying exclusion criteria, and 35, 483 controls were chosen and then matched (1:1) to osteoporosis patients based on age, sex, health insurance coverage, depression diagnosis in the past, and follow-up duration after index date. The analyses of depression-free survival were carried out using Kaplan-Meier curves and log-rank tests. Cox proportional hazards models (dependent variable: depression) were used to adjust for confounders. Results Depression diagnoses were presented in 33.0 % of the osteoporosis group and 22.7 % of the control group after the 5-year follow-up (p  < 0.001). Dementia, cancer, heart failure, coronary heart disease, and diabetes were associated with a higher risk of developing depression (p  < 0.001). Private health insurance was associated with a lower risk of depression. There was no significant effect of fractures on depression risk. Conclusion The risk of depression is significantly increased for patients with osteoporosis in primary care practices within Germany.